Effective elastic–plastic response of two-phase composite materials of aligned spheroids under uniaxial loading. (February 2018) - Teng, Hong
Highlights: Double-inclusion model for the uniaxial elastic–plastic response of a two-phase composite of aligned spheroids is presented. Matrix is treated as a two-phase material consisting of elastic and plastic regions. Model predictions agree well with available exact and experimental results. Abstract: In this study the incremental elastic–plastic double-inclusion model previously developed for two-phase particulate composites of spherical particles is extended to two-phase particulate composites of aligned spheroidal particles. The study is limited to the effective elastic–plastic response under uniaxial loading of composites consisting of purely elastic particles and elastic–plastic matrix of the von Mises yield criterion with isotropic strain hardening. The incremental elastic–plastic double-inclusion model is formulated through the use of the matrix tangent moduli, and evaluated by comparison of the model predictions with the exact results of the direct approach using representative volume elements containing many particles, and with available experimental results. It is shown that the incremental elastic–plastic double-inclusion formulation gives good prediction of the effective elastic–plastic response of two-phase composites of aligned spheroidal particles under uniaxial loading at moderate particle volume fractions. A unique feature of the present study is that during elastic–plastic deformation the composite matrix is treated as a two-phase material consisting of both an elastic and a plastic region.